Wayne Fenton's Impact on Academic Neuroscience - Geyer, Mark A. (Oxford University Press, 2007)
The legacy of Wayne Fenton will undoubtedly include his broad impact upon the academic community of researchers in psychiatry and neuroscience. Although this impact has already been felt, its full breadth and depth can only be anticipated. Eventually, the most profound impact of Wayne Fenton's legacy will likely be the one Wayne most fervently desired: that people with psychiatric disorders receive better and more effective treatments for their illnesses. By virtue of the MATRICS initiative, this impact will begin in the context of treatments for the cognitive deficits in schizophrenia, which is currently a critical unmet need. Within academic settings, this specific impact is already evident as a resurgence of interest in the neurobiology and pharmacology relevant to cognitive dysfunction in schizophrenia. As envisioned by Wayne Fenton, however, the impact of MATRICS and the other programs he initiated will be broader than “only” the treatment of cognitive deficits in schizophrenia. His vision was to target a drug treatment to an individual symptom domain, individualizing treatment regimens for each patient, without requiring a drug to be effective in all domains. Thus, the particular target of opportunity that provided Wayne Fenton's focus in the initiation of the MATRICS program is already having an important impact, but in the longer term these efforts will no doubt lead to parallel developments and improvements in the treatment of other psychiatric disorders.